2017
DOI: 10.1080/10942912.2016.1230873
|View full text |Cite
|
Sign up to set email alerts
|

Comparative study of potato protein concentrates extracted using ammonium sulfate and isoelectric precipitation

Abstract: In this study, effects of NaCl concentrations (0.0, 0.2, 0.4, 0.6, 0.8, and 1.0 M) and pH (3.0, 5.0, 7.0, and 8.0) on the physico-chemical and functional properties of potato protein concentrates extracted from potato fruit juice (PFJ) using ammonium sulfate precipitation (ASP) and isoelectric precipitation (IEP) were investigated. The total polyphenol content of potato protein concentrates extracted by IEP (IEPP) was 2.5 times of that of potato protein concentrates extracted by ASP (ASPP), which resulted in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
19
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(23 citation statements)
references
References 39 publications
3
19
0
1
Order By: Relevance
“…Although the analyzed samples are from a single harvest, which can be considered a limitation of the study, the chemical composition of these ingredients was consistent with previously reported values. A study evaluating POP concentrates processed using ammonium sulfate precipitation or isoelectric precipitation reported higher CP values of 85.4% and 88.8% (DMB), respectively ( Zhang et al, 2017 ). The CP content of POP is higher than what is typically observed in protein concentrates.…”
Section: Resultsmentioning
confidence: 99%
“…Although the analyzed samples are from a single harvest, which can be considered a limitation of the study, the chemical composition of these ingredients was consistent with previously reported values. A study evaluating POP concentrates processed using ammonium sulfate precipitation or isoelectric precipitation reported higher CP values of 85.4% and 88.8% (DMB), respectively ( Zhang et al, 2017 ). The CP content of POP is higher than what is typically observed in protein concentrates.…”
Section: Resultsmentioning
confidence: 99%
“…In addition to serving as a major nutrient source, potato starch is also an important industrial food ingredient. A by-product of the potato starch industry is potato fruit juice (PFJ) which contains proteins, amino acids and peptides ( Zhang et al, 2017 ). While PFJ has a high nutritional value, vegetable proteins, including potato, contain many anti-nutritional components and thus must be refined prior to human consumption ( Steinhof et al, 2005 ).…”
Section: Introductionmentioning
confidence: 99%
“…Drying the biomass was achieved using a direct contact rotary dryer. The compressor used to provide air to the bioreactor was designed to provide an aeration of 0.04 vvm, and was calculated using Equation (4). The costs of the equipment are presented in Table 6.…”
Section: Economic Analysismentioning
confidence: 99%
“…They include thermal coagulation, acid precipitation, salting out, isoelectric precipitation, complexing with carboxymethylcellulose or bentonite, ultrafiltration, expanded bed adsorption and dry separation [3][4][5][6]. However, the only method that is presently being used for industrial recovery of protein from PL is heat coagulation [3][4][5][6][7]. In this method, steam is injected into the liquor at a pH of 5.5 to increase the temperature to 99 • C. This coagulates the proteins, which are then precipitated and collected [8].…”
Section: Introductionmentioning
confidence: 99%